What is Normal Ovarian Reserve? - Dillon, Katherine E.; Gracia, Clarisa R. (Seminars in Reproductive Medicine, 2013)
While hormonal and ultrasonographic measures of ovarian reserve are often used to counsel patients about their fertility potential, normative data for these markers in the general population are lacking. Most studies are cross sectional and take place within specific subpopulations. Antral follicle count and anti-Mullerian hormone have been shown to be the best indicators of a woman's total follicular reserve. Ovarian volume, inhibin B, estradiol, and follicle-stimulating hormone are less helpful. Antral follicle count and anti-Mullerian hormone decrease with age and have been used to attempt to predict the length of the fertile window. Additional longitudinal data are needed for these biomarkers in populations of young, healthy, multiethnic women to assess for the presence of cofactors and determine the rate of age-related decline. Currently, these biomarkers are insufficient as predictors of fertility potential or advancement to menopause and no definitive determinations can be made about what constitutes “normal” levels of each measure.
Keywords: ovarian reserve; normative data; fertility